MiR-199b-5p Suppresses Tumor Angiogenesis Mediated by Vascular Endothelial Cells in Breast Cancer by Targeting ALK1 - Xiao Lin; Xiao Lin; Xiao Lin; Wuxia Qiu; Wuxia Qiu; Wuxia Qiu; Yunyun Xiao; Yunyun Xiao; Yunyun Xiao; Jianhua Ma; Jianhua Ma; Jianhua Ma; et al. (Frontiers in Genetics, 2020)
Angiogenesis is a crucial event during cancer progression that regulates tumor growth and metastasis. Activin receptor-like kinase 1 (ALK1), predominantly expressed in endothelial cells, plays a key role in the organization of neo-angiogenic vessels. Therapeutic targeting of ALK1 has been proposed as a promising strategy for cancer treatment, and microRNAs (miRNAs) are increasingly being explored as modulators of angiogenesis. However, the regulation of ALK1 by miRNAs is unclear. In this study, we identified that ALK1 is directly targeted by miR-199b-5p, which was able to inhibit angiogenesis in vitro and in vivo. Moreover, it was found that miR-199b-5p was repressed in breast cancer cells and its expression was decreased during the VEGF-induced angiogenesis process of human umbilical vein endothelial cells (HUVECs). Overexpression of miR-199b-5p inhibited the formation of capillary-like tubular structures and migration of HUVECs. Furthermore, overexpression of miR-199b-5p inhibited the mRNA and protein expression of ALK1 in HUVECs by directly binding to its 3’UTR. Additionally, overexpression of miR-199b-5p attenuated the induction of ALK1/Smad/Id1 pathway by BMP9 in HUVECs. Finally, overexpression of miR-199b-5p reduced tumor growth and angiogenesis in in vivo. Taken together, these findings demonstrate the anti-angiogenic role of miR-199b-5p, which directly targets ALK1, suggesting that miR-199b-5p might be a potential anti-angiogenic target for cancer therapy.